1987
DOI: 10.1128/jvi.61.2.256-263.1987
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic revertants of temperature-sensitive M protein mutants of vesicular stomatitis virus: sequence analysis and functional characterization

Abstract: Twenty-five spontaneous temperature-stable revertants of four different temperature-sensitive (ts) M protein mutants (complementation group III: tsG31, tsG33, ts023, and ts089) were sequenced and tested for their ability to inhibit vesicular stomatitis virus RNA polymerase activity in vitro. Consensus sequences of the coding region of each M protein gene were determined, using total viral RNA as template. Fifteen different sequences were found among the 25 revertants; 14 differed from their ts parent by a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
29
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 34 publications
11
29
1
Order By: Relevance
“…Of considerable interest are early studies which indicate that various temperature-sensitive mutants of VSV in complementation group III contain M protein which exhibits a nonconditional loss in the phenotype for inhibition of VSV transcription (2, 29). Morita et al (14) have sequenced some of these mutants and many revertants by primer cDNA extension and found spontaneous nucleotide changes leading * Corresponding author.…”
mentioning
confidence: 99%
“…Of considerable interest are early studies which indicate that various temperature-sensitive mutants of VSV in complementation group III contain M protein which exhibits a nonconditional loss in the phenotype for inhibition of VSV transcription (2, 29). Morita et al (14) have sequenced some of these mutants and many revertants by primer cDNA extension and found spontaneous nucleotide changes leading * Corresponding author.…”
mentioning
confidence: 99%
“…Nucleotide sequencing revealed that there was a single-amino-acid difference between the NS gene segment of the 143-1 virus and the corresponding genes of the revertant viruses, a change from valine to alanine at amino acid 23 of the NS1 protein. Intragenic suppression of point mutations in ts mutants of influenza A viruses has been reported previously (18,26), as has intragenic suppression of i's and other mutations of animal viruses, including vesicular stomatitis virus, poliovirus, foot-and-mouth disease virus, vaccinia virus, and Sindbis virus (12,14,17). Intragenic suppression of a deletion mutation of an influenza virus has not been reported previously.…”
Section: Discussionmentioning
confidence: 83%
“…This membrane-budding function is also shown to be restricted by a specific site mutation in the M-gene cDNA of a VSV temperature-sensitive mutant, in which phenylalanine is substituted for leucine at amino acid 111 of the M protein. This mutation previously had been shown to be responsible for restricted production of virions at a nonpermissive temperature (11), which can also be rescued by a coexpressed revertant (10).…”
mentioning
confidence: 95%
“…We had previously also found that the M protein synthesized in cells infected with the M gene of temperature-sensitive mutant tsO23 failed to bind to plasma membrane at the restrictive temperature of 39ЊC but did so at the permissive temperature of 31ЊC (20). The M gene of tsO23 has three mutations leading to amino acid substitutions at residues 21, 111, and 227; the temperature-sensitivity restriction phenotype has been shown to be due to a Leu3Phe substitution at amino acid 111 (11). Plasmid expression of M protein with leucine at residue 111 will complement tsO23 infection by enhancing the release of virions at the restrictive temperature, but the presence of phenylalanine or other amino acids at residue 111 results in a failure to complement tsO23 infection (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation